Hospitalists as cure for hospitalism. - Goldman, Lee (American Clinical and Climatological Association, 2003)
For much of recorded history, it was difficult to document that care in a hospital improved outcomes. In fact, the term "hospitalism" was coined to describe a variety of iatrogenic maladies that were acquired by hospitalized patients and that often were more deadly than the admitting condition itself. In the modern era, the presumed benefits of hospitalization are achieved at the expense of substantial resources, but even these high costs have not eliminated iatrogenic complications. The hospitalist movement, by which a specialized group of physicians cares for inpatients, especially on medical and pediatric services, has reduced costs, generally maintained the satisfaction of all participants, and appears to have improved the quality of care. Despite concerns about discontinuity of care, hospitalists are likely to become the dominant mode of inpatient care in the United States.